The Activities of Public Libraries in the Economic Development of Society: A Systematic Review - Davoud Haseli; Zeinab Safavi; Farzaneh Parsa (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2023)
Purpose: Public libraries have historically played a role in supporting economic development, entrepreneurship, small businesses, and providing commercial information to various stakeholders. This study aims to identify the types of services, programs and economic activities that public libraries offer in this domain, based on a review of the relevant literature. Method: The present research is a systematic literature review, and the systematic study framework of Kitchenham and Charters was used to carry out it. By identifying the databases and query terms, searches were conducted and finally, by refining the sources and applying the entry and exit criteria to the research, 37 sources in English and 6 sources in Farsi were entered into the systematic review. The research tool was a checklist type. The information obtained by summarizing the contents is presented in the form of a table. Findings: The activities of public libraries for economic development were grouped into four components: information, education, social, and space and equipment. The information component consists of two dimensions: resources and databases, and reference services. The resources and databases dimension involves assessing resource needs, providing economic information services, developing economic collections, collecting job resources, resume writing and job interview skills, marketing economic collections, creating job databases, providing access to commercial law databases, and creating and maintaining economic websites. The reference services dimension offers services such as general and specialized reference and consultation, business and research reference, document delivery, remote business question answering, job search assistance, subject guides and search assistance. The education component includes developing financial literacy and entrepreneurship skills, specific skills for jobs and businesses, digital and technology literacy, skills for students and low-educated adults, business information literacy training, economic and business consultations, and coach training. The social component includes services such as community socio-economic development, creating social partnerships, networking, holding business events, organizational cooperation, and meetings with consultants. The space and equipment component includes creating innovation buildings and spaces, preparing physical spaces, creating reference spaces, independent commercial libraries, and developing equipment. Originality/value: This review examines the diverse services, programs, and activities that public libraries offer to support community economic development. The findings reveal that public libraries are developing a new function, called economic function, that encompasses various roles and dimensions, such as information, education, social issues, and space and equipment development. To address the economic challenges of the society, public libraries design and deliver various programs and services for businesses, business owners, entrepreneurs and even general users. This study enhances the existing knowledge about the economic impact of public libraries and proposes directions for future public library action.